Design and Analysis of a Process for Methane to Hydrogen Conversion Using Piston Reactor Technology - Mary Anna Katebah (AIDIC Servizi S.r.l., 2021)
The global demand for hydrogen is seeing significant growth mainly because it is a clean energy carrier. This work compares the piston reactor versus conventional flow reactor on the basis of hydrogen production via the partial oxidation route. A piston reactor is essentially a repurposed engine that is utilized as a reactor and is an emerging simple and compact technology. Advantages of piston reactors include high throughput, high temperature and pressure conditions at short residence times and rapid quenching steps. A process is synthesized and analyzed that implements the reactor for the partial oxidation of methane, including water-gas shift reactions and appropriate separation sequences to purify and maximize hydrogen production. The performance of the process is compared to that of a conventional partial oxidation process design. Results showed that the engine process results in higher hydrogen production costs compared to the conventional system. However, the piston reactor process has significant amounts of excess heat that could be applied for carbon dioxide capture and sequestration. Results showed that around 33 % lower CO2 emissions could be achieved in the piston reactor process compared to conventional partial oxidation.